2023
DOI: 10.1021/acsomega.3c01436
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity against SARS-CoV-2 of Conformationally Constrained Helical Peptides Derived from Angiotensin-Converting Enzyme 2

Abstract: Despite the availability of vaccines, COVID-19 continues to be aggressive, especially in immunocompromised individuals. Therefore, the development of a specific therapeutic agent with antiviral activity against SARS-CoV-2 is necessary. The infection pathway starts when the receptor binding domain of the viral spike protein interacts with the angiotensin converting enzyme 2 (ACE2), which acts as a host receptor for the RBD expressed on the host cell surface. In this scenario, ACE2 analogs binding to the RBD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Surprisingly, the hydrocarbon staple peptide 11 demonstrated a significantly higher inhibition efficacy than peptide 4 , which suggests that an excessive level of rigidity may be detrimental to its antiviral activity. In fact, a recent study demonstrated significantly superior antiviral activity of single-stapled peptides compared with their less-flexible, double-stapled analogues [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the hydrocarbon staple peptide 11 demonstrated a significantly higher inhibition efficacy than peptide 4 , which suggests that an excessive level of rigidity may be detrimental to its antiviral activity. In fact, a recent study demonstrated significantly superior antiviral activity of single-stapled peptides compared with their less-flexible, double-stapled analogues [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several independent research groups have focused on peptidomimetic synthesis based on the α1-helix of hACE2. They have produced peptides ranging from 9–65 residues, and their work has highlighted the direct impact of helicity on antiviral activity [ 18 , 19 , 20 , 21 , 22 , 23 ]. However, a systematic comparative study of the i , i + 4 helix-inducing constraints leading to the desired hACE2 α-helical conformation has not been conducted to date.…”
Section: Introductionmentioning
confidence: 99%
“…[65][66][67][68] We used this approach to perform a structure-activity relationship with mono-and ditriazolyl bridged peptides derived from the minimal sequence ACE2(24-42). 57 In particular, the analog clicked at position 36-40 features a more stable secondary structure and increased antiviral activity as compared to the native fragment (Entry 4, Table 1).…”
Section: Modified Peptides As Inhibitors Of Ace2-rbd Interactionmentioning
confidence: 99%
“…The presence of a second cycle results in an even greater increase in biological stability and ability to bind to the receptor, as each ring in the bicyclic structure can function independently, which makes these peptides bifunctional [21]. Thus, bicyclic peptides offer high expectations for the development of new drug candidates carriersdue to their structural similarity with proteins [22].…”
Section: Introductionmentioning
confidence: 99%